Simulation and Modeling of Nonlinear Electromagnetic Effects in Elastic Thin Plates with Complex Shapes - Bahramov Muhammadali Eraliyevich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
The paper presents a mathematical model derived from the Hamilton–Ostrogradsky variational principle. By applying the Kirchhoff–Love hypothesis, the original three-dimensional formulation is reduced to a two-dimensional model. A computational algorithm was developed to solve the governing equations, supported by custom software implementation. Numerical experiments were carried out, and the obtained results were analyzed to validate the proposed approach.